Managing indoor environments and energy in buildings with integrated intelligent systems. (2015) - Nikolaou, Triantafyllia; Kolokotsa, Dionysia; Stavrakakis, George; Apostolou, Apostolos; Munteanu, Corneliu
No abstract available